Ant diversity in a Peninsular Malaysian mangrove forest and oil palm plantation. - Hashim, Nor Rasidah; Wan Jusoh, Wan Faridah Akmal; Mohd Nasir, Mohd Nassrul Safre (Penerbit UMS, 2009)
In Malaysia, it is a common practice to convert mangrove forests into agricultural plantations, especially oil palm. The study was carried out in Rembau, Peninsular Malaysia. A total of 9 species were found in the oil palm plantations & mangrove forests. The number of species found in each sampling plot was low: 3-4 for oil palm plots & 2-4 for mangrove forest plots. Four species (Paratrechina sp., Cardiocondyla sp., Monomorium sp. 2, & Odontomachus simillimus) found in the plantation plots were absent in the mangrove plots, while 2 (Anoplolepis sp. & Pheidole sp.) found in the mangrove plots were not detected in oil palm. The 2 species most frequent in mangroves (Pseudolasius sp. & Euprenolepis sp.) were rarer in the plantations.